Analysis of ORP2‐knockout hepatocytes uncovers a novel function in actin cytoskeletal regulation. Issue 3 (3rd January 2018) - Kentala, Henriikka; Koponen, Annika; Kivelä, Annukka M.; Andrews, Robert; Li, ChunHei; Zhou, You; Olkkonen, Vesa M.
Abstract : ORP2 is implicated in cholesterol transport, triglyceride metabolism, and adrenocortical steroid hormone production. We addressed ORP2 function in hepatocytes by generating ORP2‐knockout (KO) HuH7 cells by CRISPR‐Cas9 gene editing, followed by analyses of transcriptome, F‐actin morphology, migration, adhesion, and proliferation. RNA sequencing of ORP2‐KO cells revealed >2‐fold changes in 579 mRNAs. The Ingenuity Pathway Analysis (IPA) uncovered alterations in the following functional categories: cellular movement, cell‐cell signaling and interaction, cellular development, cellular function and maintenance, cellular growth and proliferation, and cell morphology. Many pathways in these categories involved actin cytoskeleton, cell migration, adhesion, or proliferation. Analysis of the ORP2 interactome uncovered 109 putative new partners. Their IPA analysis revealed Ras homolog A (RhoA) signaling as the most significant pathway. Interactions of ORP2 with SEPT9, MLC12, and ARHGAP12 were validated by independent assays. ORP2‐KO resulted in abnormal F‐actin morphology charac‐terized by impaired capacity to form lamellipodia, migration defect, and impaired adhesion and proliferation. Rescue of the migration phenotype and generation of typical cell surface morphology required an intact ORP2 phosphoinositide binding site, suggesting that ORP2 function involves phosphoinositide binding and transport. The results point at a novel function of ORP2 as a lipid‐sensing regulator of the actin cytoskeleton, with impacts on hepatocellular migration, adhesion, and proliferation.—Kentala, H., Koponen, A., Kivela, A. M., Andrews, R., Li, C., Zhou, Y., Olkkonen, V. M. Analysis of ORP2‐knockout hepatocytes uncovers a novel function in actin cytoskeletal regulation. FASEB J. 32, 1281‐1295 (2018). www.fasebj.org